A low sidelobe 77 GHz centre‐fed microstrip patch array antenna - Qian Chen; Songlin Yan; Xinyue Guo; Wei Wang; Zhixiang Huang; Lixia Yang; Yingsong Li; Xianling Liang (IET Microwaves, Antennas & Propagation, 2023)
Abstract A low sidelobe 77 GHz centre‐fed microstrip patch array antenna is proposed for automotive radar application. The proposed antenna comprises eight linear antenna arrays, each of which is centre‐fed by a coplanar waveguide with ground transmission line at the back of the microstrip patches. Each linear antenna array contains 10 patch antenna units, which are connected through a T‐type power divider network to achieve a −30 dB Taylor weighted distribution. The simulation results show that the designed phased array antenna has a good one‐dimensional phased scanning ability of ±45° with active voltage standing wave ratio less than 2 at 75–79 GHz, along with −20 dB low sidelobe symmetrical radiation patterns in the H plane. An antenna sample fed by a WR12 waveguide is fabricated and measured to verify its performance. The measured VSWR is less than 2 at 73.6–85 GHz. This design provides a new idea for millimetre wave automotive radar antenna design.